Efektivitas Penggunaan Sosial Media Instagram Dalam Branding Brand Baru Di Malam Minggu Group - Rosalinda Manullang; Syifah Syariah (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This study aims to analyze the effectiveness of using Instagram social media in branding a new brand by Malam Minggu Group. Through the approach of marketing communication, creative branding, social media, and digital content marketing, Malam Minggu Group utilizes Instagram as a platform to market their new brand. In this study, a literature review was conducted on these concepts and an analysis was performed on the marketing strategies, branding outcomes through Instagram content, and the effectiveness of using social media in branding a new brand. The results of the study indicate that the use of Instagram social media by Malam Minggu Group effectively builds a strong brand image, increases brand awareness, and expands their brand reach. This study provides insights and recommendations to further enhance the effectiveness of using Instagram social media in branding a new brand.